Analisis Risiko K3 Menggunakan Metode HIRADC dengan Pendekatan What-If Analysis pada Pekerjaan Blasting dan Painting di PT XYZ - Syuhada, Nurul Ain; Lukman, Lukman; Parji, Parji (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Occupational Health and Safety (OHS) is a crucial aspect of the oil and gas industry due to the high potential for hazards arising from unsafe actions and unsafe conditions. This study aims to analyze OHS risks in blasting and painting activities at PT XYZ. The methods employed include HIRADC (Hazard Identification, Risk Assessment, and Determining Control) for hazard identification, and the What-If Analysis approach to evaluate various risk scenarios. Data were collected through field observations, interviews, questionnaires, and a review of company documents. The findings identified 30 potential hazards across four main activities, all of which were classified as having a moderate risk level. Following the implementation of risk control measures, all identified hazards were successfully reduced to low to moderate risk levels. These findings highlight the importance of continuous OHS system implementation to ensure workplace safety and operational sustainability